The effect of pH and dosage coagulants to optimise performance of selected natural and chemical coagulants in wastewater: a comparative studies / Nurul Huda Noor Muhammad, Ainnie Rahayu Abdullah and Dr. Norain Isa - Noor Muhammad, Nurul Huda; Abdullah, Ainnie Rahayu; Isa, Norain (2020)
Developing countries and third world countries are facing potable water supply problems because of inadequate financial resources. The cost of the water treatment process might be higher due to the unsuitable parameter used during the coagulation, flocculation and sedimentation process. Therefore, this study was conducted to determine the effect of the pH and coagulant dosage of turbidity in wastewater and to determine the optimum pH and dosage of the selected natural and chemical coagulants. Methodology of this comparative study includes identifying problem, literature reviewing, collecting data, reviewing data, analyzing parameter and discussion. As a finding for the natural coagulants, the best pH was at 7-7-5 since the better result of colloidal particle occur at neutral condition. Among seven natural coagulant, Orange Peels has a better result among the other six coagulants. It is because the colloidal particle can be further stabilized and lead to floc growth at neutral condition. Polyaluminium Chloride (PAC) shows the better result for the chemical coagulant since its pH at 7, dosage coagulant required at 19 mg/L with removal efficiency at 90.5%. Higher dosage in chemical coagulant can result higher in sludge volume. Thus, PAC shows the better performance for the chemical coagulant since it optimum condition shows the better ones compared to other chemical coagulants.